Hot Topics in Endocrinology and Metabolism - Massoud Heshmati, Hassan (IntechOpen, 2021)
The field of endocrinology and metabolism represents a complex and multifaceted specialty in medicine that may be affected by different factors. This book presents an overview of several endocrine-disrupting chemicals, especially those affecting the reproductive system and adipose tissue. It also discusses the endocrine and metabolic impacts of the COVID-19 pandemic and the pathogenesis of lipedema.